Native T1 is predictive of cardiovascular death/heart failure events and all-cause mortality irrespective of the patient’s volume status - Treiber, Julia; Hausmann, Carla S.; Wolter, Jan Sebastian; Fischer-Rasokat, Ulrich; Kriechbaum, Steffen D.; Hamm, Christian W.; Nagel, Eike; Puntmann, Valentina O.; Rolf, Andreas (Frontiers in Cardiovascular Medicine, 2023)
Background: Native T1 has become a pivotal parameter of tissue composition that is assessed by cardiac magnetic resonance (CMR). It characterizes diseased myocardium and can be used for prognosis estimation. Recent publications have shown that native T1 is influenced by short-term fluctuations of volume status due to hydration or hemodialysis. Methods: Patients from a prospective BioCVI all-comers clinical CMR registry were included, and native T1 and plasma volume status (PVS) were determined according to Hakim’s formula as surrogate markers of patient volume status. The primary endpoint was defined as combined endpoint of cardiovascular death or hospitalization for heart failure events, the secondary endpoint was defined as all cause mortality. Results: A total of 2047 patients were included since April 2017 (median [IQR]; age 63 [52 – 72] years, 33% female). There was a significant although weak influence of PVS on native T1 (=0.11, p<0.0001). Patients with volume expansion (PVS > -13%) showed significantly higher values for tissue markers than non-volume-overloaded patients (PVS  -13%) (median [IQR]; native T1 1130 [1095 -1170] ms vs. 1123 [1086 - 1166] ms, p <0.003; T2 39 [37 - 40] ms vs. 38 [36 - 40] ms, p <0.0001. In Cox regression analysis both native T1 and PVS were independently predictive of the primary endpoint and and allcause mortality. Conclusion: Despite a weak effect of PVS on native T1, its predictive power was not affected in a large, all-comers cohort.